IMPLEMENTASI KONSEP EDUPRENEURSHIP DALAM PENGELOLAAN LEMBAGA BIMBINGAN BELAJAR “ANAK HEBAT” KEDUNGWUNI KABUPATEN PEKALONGAN - M. Shidqul Wafa; Navita Putri Lestari; Fani Restian; Naily Fatikhul Izzah (CV. Denasya Smart Publisher, 2025)
This study adopts a qualitative approach with a descriptive research type, aiming to holistically describe the implementation of the edupreneurship concept in the management of the